2012
DOI: 10.1016/j.neuropharm.2012.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for involvement of nitric oxide and GABAB receptors in MK-801- stimulated release of glutamate in rat prefrontal cortex

Abstract: Systemic administration of NMDA receptor antagonists elevates extracellular glutamate within prefrontal cortex. The cognitive and behavioral effects of NMDA receptor blockade have direct relevance to symptoms of schizophrenia, and recent studies demonstrate an important role for nitric oxide and GABAB receptors in mediating the effects of NMDA receptor blockade on these behaviors. We sought to extend those observations by directly measuring the effects of nitric oxide and GABAB receptor mechanisms on MK-801-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 57 publications
1
18
1
1
Order By: Relevance
“…Under these circumstances, it is possible that the activation of AMPA receptors mediated by increased ketamine induced-glutamate neurotransmission would increase anxiety, an effect that would counteract the possible anxiolytic-like effect of ketamine mediated by blocking the NMDA receptors. On the other hand, MK-801 increased extracellular glutamate levels in the prefrontal cortex only at high doses (0.3-0.6 mg/kg) (Roenker et al, 2012;Zuo et al, 2006). Consequently, a very low dose of MK-801 like the one used in our study (0.05 mg/kg) probably did not increase glutamate levels, which resulted in an anxiolytic-like effect mediated by the exclusive NMDA receptors blockade.…”
Section: New Findingscontrasting
confidence: 50%
“…Under these circumstances, it is possible that the activation of AMPA receptors mediated by increased ketamine induced-glutamate neurotransmission would increase anxiety, an effect that would counteract the possible anxiolytic-like effect of ketamine mediated by blocking the NMDA receptors. On the other hand, MK-801 increased extracellular glutamate levels in the prefrontal cortex only at high doses (0.3-0.6 mg/kg) (Roenker et al, 2012;Zuo et al, 2006). Consequently, a very low dose of MK-801 like the one used in our study (0.05 mg/kg) probably did not increase glutamate levels, which resulted in an anxiolytic-like effect mediated by the exclusive NMDA receptors blockade.…”
Section: New Findingscontrasting
confidence: 50%
“…It has been reported that MK‐801 and PCP stimulate cortical glutamate release in PFC and hippocampus . In this scenario, rac‐BHFF could counteract the disinhibition of neuronal activity produced by exaggerated NMDAR stimulation in these areas or, alternatively, modulate distinct forebrain pathways under the control of non‐NMDA glutamatergic receptors, such as AMPA and kainate .…”
Section: Discussionmentioning
confidence: 99%
“…One explanation could be that there is release of glutamate from the brain after MK-801 administration [44,45]. Since the uptake of 'use-dependent' antagonists is thought to be related to the amount of glutamate in the brain [46], it could be that injection of MK-801 increased the release of glutamate, opening more NMDAR ion channels, and resulting in higher uptake of [ 11 C]21, [ 11 C]23 and [ 18 F]26 than at baseline.…”
Section: Pre-treatment Studiesmentioning
confidence: 99%